Penggunaan Metode Thinning dalam Pengolahan Citra - Ari Endang Jayati (Jurnal Ilmiah Dinamika Teknik, 2008)
In image processing to get the desired image, there are many ways to manipulate it. Thinning (which is called skeletonizing) is a method to represent the image transformation to a graph shape by reducing the particular information in image. Thinning method can be implemented in OCR (Optical Character Recognition) industry and forestry. There are many algorithm to apply this method, in the meanwhile Thinning Binary Regions Algorithm